The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/j.jcrs.2011.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of corneal light scattering after corneal collagen crosslinking

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 27 publications
2
5
0
1
Order By: Relevance
“…On the contrary, a symmetrical treatment pattern (CXL in the present study) also gives a symmetrical treatment effect. In accordance with our previous reports,15 18 this study shows that the increase in corneal densitometry relates to the CXL treatment effect, which is in alignment with recent in vivo confocal microscopy findings, where the phenomenon of light scattering is explained as an ‘indirect sign of CXL-induced stromal collagen compaction and remodeling’ 19. Accordingly, with an asymmetrical treatment pattern as in the present study, an increase in corneal densitometry is seen only where the cornea is crosslinked, but not outside the treatment zone.…”
Section: Discussionsupporting
confidence: 93%
“…On the contrary, a symmetrical treatment pattern (CXL in the present study) also gives a symmetrical treatment effect. In accordance with our previous reports,15 18 this study shows that the increase in corneal densitometry relates to the CXL treatment effect, which is in alignment with recent in vivo confocal microscopy findings, where the phenomenon of light scattering is explained as an ‘indirect sign of CXL-induced stromal collagen compaction and remodeling’ 19. Accordingly, with an asymmetrical treatment pattern as in the present study, an increase in corneal densitometry is seen only where the cornea is crosslinked, but not outside the treatment zone.…”
Section: Discussionsupporting
confidence: 93%
“…More importantly, however, increased corneal light scattering on Scheimpflug À0.3 AE 2.7 À0.2 AE 2.5; p = 0.41 0.1 AE 2.3; p = 0.05 À0.7 AE 1.9; p = 0.51 À0.7 AE 1.9; p = 0.36 À0.7 AE 1.9; p = 0.15 Cylinder (D) À3.1 AE 2.1 À3.3 AE 2.1; p = 0.49 À3.1 AE 2.2; p = 0.70 À0.4 AE 0.4; p < 0.01 À0.4 AE 0.4; p < 0.01 À0.5 AE 0.4; p < 0.01 SphEq (D) À1.9 AE 2.8 À1.8 AE 2.5; p = 0.65 À1.4 AE 2.4; p = 0.03 À0.9 AE 1.9; p = 0.09 À0.9 AE 1.9; p = 0.10 À0.9 AE 1.8; p = 0.30 BSCVA (logMar) CXL = conventional corneal crosslinking, CXL ctrl = control subjects to patients treated with CXL, CRXL = corneal crosslinking with mechanical compression of the cornea, CRXL ctrl = control subjects to patients treated with CRXL, SphEq = spherical equivalent, calculated as sphere+cylinder/ 2, BSCVA = best spectacle-corrected visual acuity, logMar = logarithm of the minimum angel of resolution, K max = maximum keratometry value, obtained with the Pentacam â HR, CT min = corneal thickness at the thinnest point, obtained with the Pentacam â HR. photography, previously used as an indicator of the corneal response after CXL by our group (Beckman Rehnman et al 2011), was a consistent finding after both treatments, which indicates that a crosslinking effect did take place in all our subjects, although longitudinal long-term follow up is the only way to quantify this effect. Assessment of the light scattering data, as well as long-term follow up, will be subjects of a future study.…”
Section: Discussionsupporting
confidence: 79%
“…The mechanism underlying the continuing corneal flattening up to 2 years after corneal crosslinking has still not been entirely elucidated (Goldich et al 2012). It has been repeatedly shown that crosslinking halts the progression of keratoconus, and the effects from corneal crosslinking have been convincingly demonstrated in vitro by biochemical (Spoerl et al 2004b;Brummer et al 2011), biomechanical (Wollensak et al 2003b;Knox Cartwright et al 2012;Dias et al 2013), structural (Wollensak et al 2004;Beckman Rehnman et al 2011) and thermomechanical (Spoerl et al 2004a) investigations. Demonstrating an increased biomechanical strength in vivo after CXL treatment using the Ocular Response Analyser (ORA), has been more difficult (Vinciguerra et al 2010;Spoerl et al 2011;Gkika et al 2012;Goldich et al 2012), but it is generally accepted today that CXL acts through an increase in corneal biomechanical strength (Beshtawi et al 2013).…”
Section: Discussionmentioning
confidence: 94%
“…Variation in corneal surface smoothness and anterior transparency can affect corneal light backscatter, which can be estimated by different approaches, such as optical coherence tomography, Scheimpflug photography, and psychophysical methods (glare testing, adaptive optics visual simulator with diffuser, direct compensation method). 16 , 27 29 We found a significant decrease in both peak and average corneal light back-scattering by Scheimpflug imaging in the study group. The decrease in corneal light backscatter was highly correlated with corneal deswelling.…”
Section: Discussionmentioning
confidence: 61%